Metro‐SMHOP 01: Metronomics combination with cyclophosphamide‐etoposide and valproic acid for refractory and relapsing pediatric malignancies. Issue 9 (13th July 2020) - El kababri, Maria; Benmiloud, Sarra; Cherkaoui, Siham; El houdzi, Jamila; Maani, Khadija; Ansari, Nawal; Khoubila, Nissrine; Kili, Amina; El khorassani, Mohammed; Madani, Abdellah; Tazi, Mohammed Adnane; Ahid, Samir; et al.
Abstract: Background: In low‐ and middle‐income countries, therapeutic options for advanced, refractory, or relapsing malignancies are limited due to local constraints such as cost of drugs, distance from oncology centers, and lack of availability of new anticancer drugs. Metronomics, which combines metronomic chemotherapy (MC) and drug repositioning, allows for the provision of new therapeutic options for patients in this setting. Aim of the study: To evaluate the activity and toxicity of a metronomic regimen in Moroccan pediatric patients with refractory or relapsing malignancies. Patients and methods: From July 2014 to January 2018, patients with refractory/relapsing solid tumors treated in five pediatric oncology centers were consecutively enrolled. The metronomic regimen consisted of 28‐day cycles with daily oral administration of cyclophosphamide (30 mg/m 2 ) from days 1 to 21, together with oral etoposide (25 mg/m 2 ) from days 1 to 21 followed by break of one week and daily valproic acid (20 mg/kg) from days 1 to 28. Results: Ninety‐eight children (median age, 8 years) were included. Underlying malignancies were neuroblastoma (24 patients), Ewing sarcoma (18), osteosarcoma (14), rhabdomyosarcoma (14), and miscellaneous tumors (28). A total of 557 cycles were given (median: 6; range, 1‐18 cycles). One‐year progression‐free survival of our patients was 19%, and one‐year overall survival was 22%. Complete response was obtained in three cases (3%), partial response in 11 cases (11%), and tumor stabilization for more than six months in 28 cases (28%). Conclusion: This three‐drug metronomic combination was well tolerated and associated with tumor response and disease stabilization in 42 patients even for a long period.